LANGUAGE VARIATION AND CULTURAL IDENTITY OF THE FIRST SEMESTER LAW DEPARTMENT STUDENTS IN UNIVERSITAS PAMULANG - Retnawati, Saptina; Taman, Purwanti (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
The purpose of this study is to analyze language variations in terms of speakers and to identify cultural identity aspects of Law Department Students in the first semester in Pamulang University. There were in total 18 students who originally came from different backgrounds of areas such as Java, Banten Province, East Nusa Tenggara, and Lampung. Some of them also resided in Papua. The analysis of the study was limited to language variation in terms of speakers which consists of idiolect, dialect, chronolect, dan sociolect and some cultural identity aspects. The data was mainly gathered by observations during synchronous learning by using google meet platform. The researchers recorded the learning process in order to get several conversations between students and lecturer and among students in their break time and during the learning process. Those conversations were then analyzed based on language variations in terms of speakers and cultural identity aspects. Beside observations, some interviews were also conducted to get deeper information regarding language variations and students’ cultural identity. The observations and interviews were obviously conducted to refer to guidelines and rubrics of observations and interviews. To analyze the data, the researchers used the concept of data analyses suggested by Miles and Huberman. They divided the process of analysis into three phases consisting of data reduction, data displays, and conclusion drawing/verification.